Pengembangan Metode Pembelajaran Berbasis Aplikasi Kinemaster pada Era Pembelajaran Daring Di Universitas Dharmawangsa - M. Arif Rahman; Suhariyanti Suhariyanti; Rani Rahim (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Decree of the Minister of Education and Culture No. 4 of 2020 provides a policy on learning series in an emergency due to the spread of Covid-19, teaching and learning activities are shifted to online or online learning at their respective homes. Online learning makes use of multimedia technology, video, virtual classes, animated online text, voicemail, email, telephone conferences, and online video streaming. Online learning includes a program of organizing learning classes to reach massive and broad groups through the internet network. Online learning is a solution in the midst of the COVID-19 pandemic that is used to plan appropriate and efficient learning processes in order to achieve learning objectives well so that the learning experience of students is memorable and can achieve learning goals. The role of technology in education as an innovative creative opportunity for educators to realize a fun, orderly and conducive teaching and learning process by utilizing methods. The learning method is a way or technique of presenting lesson materials that will be used by educators when presenting lesson materials, either individually or in groups. There are several problems faced by students when learning online such as: difficulty in mastering the material due to the learning process, less creative in doing assignments, lack of understanding in planning, managing assignments before presentation, internet network is not optimal. The results of these observers need changes to achieve online learning. Utilize learning methods with applications. Kinemaster as an application that can be used in the online learning process. The Kinemaster application is a video editing application that has many features that make it easier to edit videos, especially creative and interesting learning videos so that students don't get bored, and can play videos of learning material from lecturers many times. The method developed using the Kinemaster application. This type of research uses R & D with the development model of Thiagarajan, Semmel and Semmel, namely the 4-D model. The learning method developed must be feasible and effective and can improve student learning outcomes.